Magnetic Resonance Imaging and Biomechanical Analysis of Adipose-derived Stromal Vascular Fraction Applied on Rotator Cuff Repair in Rabbits - Liang-Yu Lu; Chun-Yan Kuang; Feng Yin (Chinese Medical Journal, 2018)
Background: Adipose-derived stromal vascular fraction (ADSVF) can be applied to repair tendon and ligament tears. ADSVF treatment has a better therapeutic potential than adipose stem cells alone in promoting the healing of connective tissue injury in rabbit models. Magnetic resonance imaging (MRI) and biomechanical testing were used in this study to evaluate the efficiency of SVF in the healing of tendon-bone interface of a rotator cuff injury after reattachment. Methods: A total of 36 rabbits were studied between March and June 2016, 18 rabbits received the SVF-fibrin glue (SVF-FG) treatment and the other 18 formed the control group. ADSVF was isolated from each rabbit. A bilateral amputation of the supraspinatus tendon and parallel reconstruction was also performed on all the 36 rabbits. Then, a mixture of SVF and FG was injected into the tendon-bone interface of the SVF-FG group, whereas the control group only received FG. The animals were randomly sacrificed at 4, 8, and 12 weeks after surgery (n = 6 per group), respectively. The shoulders were prepared for MRI scanning and analysis of biomechanical properties. Analyses of variance were performed using SPSS 13.0. Results: MRI scanning showed that the signal-to-noise quotient of the SVF-FG group was not significantly higher than that of the control group at either 4 (20.1 ± 3.6 vs. 18.2 ± 3.4, F = 1.570, P = 0.232) or 8 weeks (20.7 ± 3.3 vs. 18.0 ± 3.0, F = 2.162, P = 0.117) posttreatment, and only became significant after 12 weeks (27.5 ± 4.6 vs. 22.1 ± 1.9, F = 4.968, P = 0.009). Biomechanical properties such as the maximum load, maximum strength, and the stiffness for the SVF-FG group were significantly greater than that for the control group at 8 weeks' posttreatment (maximum load: 166.89 ± 11.62 N vs. 99.40 ± 5.70 N, P < 0.001; maximum strength: 8.22 ± 1.90 N/mm vs. 5.82 ±0.68 N/mm, P < 0.010; and the stiffness: 34.85± 3.00 Pa vs. 24.57± 5.72 Pa, P < 0.010). Conclusion: Local application of ADSVF might lead to better tendon-bone healing in rabbit models.